PEMIKIRAN TEOLOGIS KAUM SALAFÎ: Studi atas Pemikiran Kalam Ibn Taymiyah - Washil, Izzuddin; Fata, Ahmad Khoirul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
In the field of kalam (Islamic theology), some major themes, like attributes of Allah, will of Allah and human freedom, or Quran as words of Allah, have become debate topics between thought schools of kalam in Islam. Because of the complexity of those topics, the debate becomes eternal, without an agreed end. Among those thought schools of kalam in Islam involved in the debate is salaf school, held by Ibn Taymiyah. In his opinion, the school is the right one because it quite conforms to Quran and sunna. By way of thought (manhaj) of salaf school, Ibn Taymiyah also takes part in explaining those major themes in his works. In the case of the will of Allah and human freedom, for example, he doesn’t agree with the Qadarite school’s thought and the Jabarite school’s thought although in this he hasn’t yet stretched out a convincing explanation. This essay will analyze the way of thought (manhaj) of salaf school and Ibn Taymiyah’s opinion about those major themes, especially in his book Majmû‘ al-Fatâwâ.